2016
DOI: 10.1016/j.bbmt.2016.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cumulative Steroid Dose with Risk of Infection after Treatment for Severe Acute Graft-versus-Host Disease

Abstract: This study aimed to characterize the incidence and risk factors of invasive fungal disease, cytomegalovirus infection, other viral diseases, and gram-negative rod infection after glucocorticoid treatment for severe acute graft-versus-host disease (GVHD) after allogeneic hematopoietic cell transplantation and to elucidate the associations of cumulative steroid dose with the risks of individual infections. The study cohort included 91 consecutive patients who developed maximum grades III and IV acute GVHD at our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 29 publications
3
28
1
1
Order By: Relevance
“…Although acute GVHD and systemic steroid have been reported to be risk factors for invasive fungal infection after HSCT, the cumulative steroid dose was not associated with fungal infection in our study. All patients in our hospital continued prophylactic treatment with antifungal drugs according to the risk of fungal infection, following Japanese and European guidelines .…”
Section: Discussionsupporting
confidence: 88%
“…Although acute GVHD and systemic steroid have been reported to be risk factors for invasive fungal infection after HSCT, the cumulative steroid dose was not associated with fungal infection in our study. All patients in our hospital continued prophylactic treatment with antifungal drugs according to the risk of fungal infection, following Japanese and European guidelines .…”
Section: Discussionsupporting
confidence: 88%
“…The results shown by Ruutu et al [9,19] and us in the present study suggest that except for the lower total dose of corticosteroid itself, prophylaxis with corticosteroids may decrease infection rates via significantly reducing the incidence of GVHD. Overall, the present results indicate that low-dose glucocorticoid prophylaxis might decrease the incidence of infections via reducing GVHD and the total dose of glucocorticoid used without compromising immune recovery ( Supplementary Table 1S), both of which might contribute to decreased infection-related mortality as described by others [13].…”
Section: Discussionsupporting
confidence: 77%
“…A number of studies have shown that reduction in infection rate contributed to the improvement of outcomes after allo-SCT [12,13,34]. Here, we indicated that a low incidence of HZV infection in patients receiving low-dose corticosteroid prophylaxis might be related to the rapid recovery of CD4 + T cells ( Supplementary Table 1S), particularly CD4 + na€ ıve T cells, as previous studies have shown that viral reactivations were associated with the kinetics of immune recovery, particularly CD4 + T cells [35À37].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic corticosteroid is also a well-known risk factor for infectious complications [7,11]. A recent study [24] revealed that the cumulative incidence rate of gram-negative rod bacteremia was 20% at 6 months after glucocorticoid treatment against severe acute GVHD; the median number of days from initiation of corticosteroids to the onset of gram-negative rod bacteremia was 55 (range, 10 to 579). We obtained a similar result in which 43 of 316 allo-HSCT recipients developed a PE-BSI at a median of 48Àdays after steroid treatment (Table 3).…”
Section: Discussionmentioning
confidence: 99%